Scenic values of developing city in Polish spatial planning system. Example of Rzeszów - Wójcik-Popek, Agnieszka; Jaworska, Agata; Kołodziej-Marek, Łucja (Zakład Architektury Krajobrazu, Wydział Biologiczno-Rolniczy, Uniwersytet Rzeszowski, 2018)
The binding spatial planning system in Poland includes the protection of scenic values in an insufficient way. The progressive, rapid urbanization threatens the existing points and planes of passive exposure, lowering the scenic and landscape values. The paper compares various definitions of landscape and landscape values and analyzes the provisions of the current Study of Conditions and Directions of Spatial Development of the municipality of Rzeszów in terms of the identification and protection of scenic values and compares attractive landscapes with the coverage of the Local Spatial Development Plan.

Obowiązujący w Polsce system planowania przestrzennego w sposób niedostateczny uwzględnia ochronę walorów widokowych. Postępująca, gwałtowna urbanizacja zagraża istniejącym punktom i płaszczyznom ekspozycji biernej, obniżając walory widokowe i krajobrazowe. W artykule zestawiono różne definicje krajobrazu i walorów krajobrazowych oraz przeanalizowano przepisy aktualnie obowiązujących Studium Uwarunkowań i Kierunków Zagospodarowania Przestrzennego gminy miasto Rzeszów pod kątem identyfikacji i ochrony walorów widokowych oraz porównano tereny atrakcyjne krajobrazowo z pokryciem MPZP.
Keywords: landscape protection; city development; spatial planning; ochrona krajobrazu; rozwój miasta; planowanie przestrzenne